Generation of bone grafts using cryopreserved mesenchymal stromal cells and macroporous collagen-nanohydroxyapatite cryogels - Rogulska, Olena Y; Trufanova, Nataliya A; Petrenko, Yuriy A; Repin, Nikolay V; Grischuk, Victor P; Ashukina, Nataliya O; Bondarenko, Stanislav Y; Ivanov, Gennadiy V; Podorozhko, Elena A; Lozinsky, Vladimir I; Petrenko, Alexander Y (Journal of biomedical materials research. Part B, Applied biomaterials, 2022)
Bone tissue engineering strategy involves the 3D scaffolds and appropriate cell types promoting the replacement of the damaged area. In this work, we aimed to develop a fast and reliable clinically relevant protocol for engineering viable bone grafts, using cryopreserved adipose tissue-derived mesenchymal stromal cells (MSCs) and composite 3D collagen-nano-hydroxyapatite (nanoHA) scaffolds. Xeno- and DMSO-free cryopreserved MSCs were perfusion-seeded into the biomimetic collagen/nanoHA scaffolds manufactured by cryotropic gelation and their osteoregenerative potential was assessed in vitro and in vivo. Cryopreserved MSCs retained the ability to homogenously repopulate the whole volume of the scaffolds during 7 days of post-thaw culture. Moreover, the scaffold provided a suitable microenvironment for induced osteogenic differentiation of cells, confirmed by alkaline phosphatase activity and mineralization. Implantation of collagen-nanoHA cryogels with cryopreserved MSCs accelerated woven bone tissue formation, maturation of bone trabeculae, and vascularization of femur defects in immunosuppressed rats compared to cell-free collagen-nanoHA scaffolds. The established combination of xeno-free cell culture and cryopreservation techniques together with an appropriate scaffold design and cell repopulation approach accelerated the generation of viable bone grafts.
Keywords: buněčná diferenciace; Tissue Engineering; kryoprezervace; osteogeneze; Cryopreservation; tkáňové inženýrství; Osteogenesis; Tissue Scaffolds; krysa rodu Rattus; kolagen; Cryogels; zvířata; Cells, Cultured; proliferace buněk; Collagen; tkáňové podpůrné struktury; mezenchymální kmenové buňky; kultivované buňky; Cell Proliferation; Cell Differentiation; Rats; kryogely; Animals; Mesenchymal Stem Cells